2016
DOI: 10.1158/0008-5472.can-15-1576
|View full text |Cite
|
Sign up to set email alerts
|

Redirecting Transport of Nanoparticle Albumin-Bound Paclitaxel to Macrophages Enhances Therapeutic Efficacy against Liver Metastases

Abstract: Current treatments for liver metastases arising from primary breast and lung cancers are minimally effective. One reason for this unfavorable outcome is that liver metastases are poorly vascularized, limiting the ability to deliver therapeutics from the systemic circulation to lesions. Seeking to enhance transport of agents into the tumor microenvironment, we designed a system in which nanoparticle albumin-bound paclitaxel (nAb-PTX) is loaded into a nanoporous solid multistage nanovector (MSV) to enable the pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
88
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 45 publications
8
88
0
Order By: Relevance
“…In contrast, the MSV-nAb-PTX therapy is projected to achieve a 71% radius decline by treatment completion. The order of magnitude of the endpoints from the in silico results (Fig 6c) are in agreement with a comparable in vivo study (Fig 6d) we have recently reported 19 . By the end of 9 days, the tumor diameter after in silico treatment with nAb-PTX and MSV-nAb-PTX was 2.9- and 14.1-fold of the untreated control, respectively (Fig 6c), while the in vivo results showed regression of 3.7- and 17.1-fold, respectively (Fig 6d).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, the MSV-nAb-PTX therapy is projected to achieve a 71% radius decline by treatment completion. The order of magnitude of the endpoints from the in silico results (Fig 6c) are in agreement with a comparable in vivo study (Fig 6d) we have recently reported 19 . By the end of 9 days, the tumor diameter after in silico treatment with nAb-PTX and MSV-nAb-PTX was 2.9- and 14.1-fold of the untreated control, respectively (Fig 6c), while the in vivo results showed regression of 3.7- and 17.1-fold, respectively (Fig 6d).…”
Section: Resultssupporting
confidence: 92%
“…Previously 19 , we designed a multistage system in which nanoparticle albumin bound paclitaxel (nAb-PTX) was packaged into solid particles to increase interaction with macrophages. nAb-PTX is clinically employed for therapy of advanced breast tumors 20, 21 , although its efficacy with liver metastasis is usually lacking and can cause hepatic toxicity 22 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paclitaxel (PTX), a chemotherapeutic agent, is widely used against several types of solid tumors besides breast, ovarian, lung, colon, head, neck, and liver cancers. [21][22][23][24][25][26][27] PTX disrupts the tubulin-microtubule equilibrium, which is different from conventional anticancer drugs affecting nucleic acid synthesis to induce cancer cell death. 28,29 It is considered as an appropriate candidate for chemotherapy because PTX at low concentrations can exert antiangiogenic activity.…”
Section: Introductionmentioning
confidence: 99%